Students’ Behavioral Intentions Regarding the Future Use of Quantitative Research Methods - Tominc, Polona; Krajnc, Maruša; Vivod , Klavdija; Lynn, Monty; Frešer, Blaž (Naše gospodarstvo/Our economy, 2018)
Changes regarding the importance of graduates’ competences by employers and changes of competences themselves are to a great extend driven by the technological changes, digitalization, and big data. Among these competences, the ability to perform business and data analytics, based on statistical thinking and data mining, is becoming extremely important. In this paper, we study the relationships among several constructs that are related to attitudes of economics and business students regarding quantitative statistical methods and to students’ intention to use them in the future. Findings of our research provide important insights for practitioners, educators, lecturers, and curricular management teams.